2021
DOI: 10.3389/fpsyg.2021.670722
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Sided Lockdown? Social Class Variations in the Implementation of Homeschooling During the COVID-19 Lockdown

Abstract: The COVID-19 pandemic deeply affected how schools and families functioned through most of 2020. In particular, school closures meant parents took on a more central role in their children’s learning. This study analyzed social class variations in the quantity and quality of homeschooling during the lockdown. Through an online questionnaire, 360 parents reported (1) their digital equipment and use, (2) the perceptions of their ability to homeschool their children, (3) how they handled homeschooling and (4) the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…Many single parents (and those from single-income families) had to maintain the work-family balance with few supports. Some researchers caution that the long-term effects of the pandemic may further widen existing inequalities in income and poverty, education and skills, and intergenerational inequalities, particularly children (including vulnerable children), families with children and young people (British Academy, 2021 ; Horowitz et al, 2021 ; Sanrey et al, 2021 ).…”
Section: Sociodemographic Disparities In Covid-19 Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Many single parents (and those from single-income families) had to maintain the work-family balance with few supports. Some researchers caution that the long-term effects of the pandemic may further widen existing inequalities in income and poverty, education and skills, and intergenerational inequalities, particularly children (including vulnerable children), families with children and young people (British Academy, 2021 ; Horowitz et al, 2021 ; Sanrey et al, 2021 ).…”
Section: Sociodemographic Disparities In Covid-19 Impactmentioning
confidence: 99%
“…Of note, whereas racial/ethnic/religious minorities in both countries were more likely to experience spending volatility, only Black and Hispanic (in the US) and Arab (in Israel) households were more likely to experience hardships. Sanrey et al, ( 2021 ) examined social class as a contextual factor in understanding the quantity and quality of homeschooling in France during the April 2020 lockdown. Their findings provided some evidence of a widening educational achievement gap during the first wave of the pandemic.…”
Section: Sociodemographic Disparities In Covid-19 Impactmentioning
confidence: 99%
“…But accounts of our participants suggest that not all parents had equal opportunities to engage in their children’s remote learning. This insight contradicts Sanrey et al’s (2021) conclusion: ‘the lower the parents’ social position, the more they spent time home-schooling their children’ (p. 1). For migrant parents, time constraints can be an expression of restrictive capital interaction.…”
Section: Findings and Discussion: Naming The Challenges Migrant Paren...mentioning
confidence: 80%
“…In contrast, children from disadvantaged social positions face disjuncture, which could lead to disengagement from the learning process. Recent studies also showed that social position variations mediate the quality and quantity of parental engagement in home-schooling (Goudeau et al, 2021; Sanrey et al, 2021).…”
Section: Conceptual Framework and Methodological Approachmentioning
confidence: 99%
“…It was associated with higher domestic conflict 11 , academic backwardness 12 , increased anxiety and suicidal behaviors 13 , 14 . The difficulties associated with homeschooling may have exacerbated inequalities in terms of economic, numerical and cultural disparities between social groups, acting as additional factors for worsening mental health in children 15 . Although the specific effect of homeschooling on children’s mental health was difficult to isolate, since it was included in a vast array of mitigation strategies, some studies reported that symptom intensity of mental health disorders varies in phase with the periods of homeschooling/school reopening 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%